Prognostic relevance of mitral and tricuspid regurgitation after transcatheter aortic valve implantation: Impact of follow-up time point for decision-making - Bäz, Laura; Möbius-Winkler, Sven; Diab, Mahmoud; Kräplin, Thomas; Westphal, Julian G.; Ibrahim, Karim; Schulze, P. Christian; Franz, Marcus (Frontiers in Cardiovascular Medicine, 2023)
Background: The coexistence of both, mitral and tricuspid regurgitation (MR, TR) in patients undergoing transcatheter aortic valve implantation (TAVI) and their dynamics after TAVI is likely to be of prognostic relevance. Aims: The current study was aimed to identify predictors of long-term mortality assessed before and after TAVI with special focus on MR and TR. Methods: A total of 445 patients treated by transfemoral TAVI were included and evaluated at baseline as well as 6 to 8 weeks and 6 months after TAVI. Results: Moderate or severe (relevant) MR occurred in 39% and relevant TR in 32% of the patients at baseline. After 6 to 8 weeks, these rates were 27% for MR (p=0.001) and 35% for TR (p=n.s.). For relevant MR, the rate after 6 months was 28% (p=0.036, compared to baseline) and 34% for relevant TR (p=n.s., compared to baseline). Multivariate analysis identified the following independent predictors of 2-year mortality: sex, age, AS entity, atrial fibrillation, renal function, relevant TR, systolic pulmonary artery pressure (PAPsys) and six-minute walk distance at baseline; clinical frailty scale and PAPsys at 6 weeks and BNP as well as relevant MR at 6 months after TAVI. Kaplan-Meier analysis displayed significantly worse 2-year survival rates in patients suffering from relevant TR at baseline (31.6% versus 17.4%, p<0.001) as well as those with relevant MR at 6 months (12.1% versus 4.8%, p=0.042). Conclusion: The results of this real-life experience demonstrate the prognostic importance of accurate and repeated evaluation of mitral and tricuspid regurgitation in TAVI patients.